The influence of growth sales, capital structure and corporate governance on financial performance of consumer non-cyclical firms in Indonesia - Yeni, Fitri; Hadi, Hamdy; Elfiswandi, Elfiswandi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to discover the relationship between growth sales, capital structure, and corporate governance on financial performance of consumer consumer non-cyclical firms in Indonesia. Financial performance is observed from market performance (Tobin's Q) and profitability performance (ROA). The population in this study is firms in consumer consumer non-cyclical on Indonesia Stock Exchange. The total population is 113 firms. 39 firms were selected as samples. The data is obtained from the annual report which starts from the period 2018 to 2022. A total of the population was determined as samples by purposive sampling method. Data analysis using panel data regression. The result shows: 1) Growth Sales have a significant influence on market performance; however, it does not have a significant effect on profitability performance. 2) Capital Structure significantly influences market and profitability performance 3) Corporate governance significantly influences market and profitability performance. Suggestions for companies that must strive to increase sales, maintain good corporate governance and pay attention to the company's capital structure in a balanced manner.